COMPUTATIONAL THINKING ABILITY STUDENTS BASED ON GENDER IN CALCULUS LEARNING - Triana Harmini; Pradipta Annurwanda; Siti Suprihatiningsih (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The purpose of this study was to determine differences in the computational thinking skills of first students of the Department of Informatics Engineering based on genders. This study uses quasi-experimental methods. The subjects in this study were semester two students of the Department of Informatics Engineering in 2019/2020. The research subjects were 34 male students and 23 female students. Methods of data collection using tests and observations. The research instrument used was a computational thinking ability test and an observation sheet. Data analysis using a t-test (independent sample) with analysis prerequisites in normality and homogeneity tests. Test analysis utilizing the help of IBM SPSS Statistics 20. The study of research data shows that there are significant differences between the computational thinking ability of male and female students. The average results of the computational thinking ability test showed that male students' computational thinking ability is better than the female students' computational thinking ability. The male and female students' computational thinking skills reach the generalization stage, where male students can find solutions directly through easy-to-understand and straightforward ideas. Meanwhile, female students can explain the flow and concepts used to solve problems. AbstrakTujuan penelitian ini adalah untuk mengetahui perbedaan kemampuan berpikir komputasi mahasiswa semester awal jurusan Teknik Informatika berdasarkan jenis kelamin. Penelitian ini menggunakan metode eksperimen semu. Subjek dalam penelitian ini adalah mahasiswa semester 2 jurusan Teknik Informatika tahun ajaran 2019/2020. Subjek penelitian adalah 34 siswa laki-laki dan 23 siswa perempuan. Metode pengumpulan data menggunakan tes dan observasi. Instrumen penelitian yang digunakan adalah tes kemampuan berpikir komputasi dan lembar observasi. Analisis data menggunakan uji-t dengan prasyarat analisis berupa uji normalitas dan homogenitas. Uji analisis menggunakan bantuan IBM SPSS Statistics 20. Hasil penelitian dapat disimpulkan bahwa terdapat perbedaan yang signifikan antara kemampuan berpikir komputasi siswa laki-laki dan perempuan. Hasil rata-rata tes kemampuan berpikir komputasi diperoleh bahwa kemampuan berpikir komputasi siswa laki-laki lebih baik daripada kemampuan berpikir komputasi siswa perempuan. Kemampuan berpikir komputasi mahasiswa putra dan putri mencapai tahap generalisasi, dimana mahasiswa putra mampu mencari penyelesaian secara langsung melalui ide sederhana dan mudah dipahami. Sedangkan mahasiswa putri mampu menjelaskan alur dan konsep yang digunakan untuk menyelesaikan masalah.